2017
DOI: 10.1159/000464270
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Paris System in Reporting Urine Cytology

Abstract: Objective: To find out the utility of The Paris System (TPS) in reporting urine cytology and to compare it with the reporting system currently used in our laboratory. Study Design: This retrospective study was undertaken over a period of 1 year during which slides of all the urine specimens sent for cytological examination were retrieved from our laboratory filling system. They were blindly reviewed and reclassified according to TPS. Surgical follow-up was obtained from the uropathology services of our departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 9 publications
8
63
1
Order By: Relevance
“…One of the objectives of this study was to examine the rate of atypia between the SJRH system, which was in use during the study period, and TPS which was implemented at our institution in February of 2017 (during the time of case review). A few other recent studies have examined TPS and have reported a reduction in cases reported as atypical . Our results are in agreement with these studies with almost a 50% reduction in AUC compared with AUS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One of the objectives of this study was to examine the rate of atypia between the SJRH system, which was in use during the study period, and TPS which was implemented at our institution in February of 2017 (during the time of case review). A few other recent studies have examined TPS and have reported a reduction in cases reported as atypical . Our results are in agreement with these studies with almost a 50% reduction in AUC compared with AUS.…”
Section: Discussionsupporting
confidence: 93%
“…In examining TPS, we are only evaluating cases that were previously diagnosed as AUS and are therefore not assessing the full scope of TPS. This might explain why sensitivity of AUC is decreased as compared with the former AUS category, whereas it is increased in other studies . Although the retrospective pathology review gives a relatively good approximation of diagnosis, it may not always be predictive of how the case would have been signed out.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…After implementation of TPS, the equivocal or “atypical” category was reduced from 29% to 13% of cases (a reduction of 55%). These findings are in keeping with data from 3 other studies that demonstrated reductions in the “atypical” category of 26%, 40%, and 57%, respectively . In addition, Hassan et al demonstrated not only a 25% reduction in “atypical” diagnoses but also a higher positive predictive value of HGUC for AUC after implementation of TPS .…”
Section: Discussionsupporting
confidence: 85%
“…This system further alters the sensitivity and specificity of urine cytology evaluations. For example, in the study of Malviya et al, using TPS, the rate of HGUC increased from 7.3% to 13%, the sensitivity rose from 68% to 95%, and the negative predictive value increased from 46% to 86% . In Das et al's study, the measured sensitivity and positive predictive value were 86.95% and 83.3%, respectively .…”
Section: Discussionmentioning
confidence: 94%